PENGENTASAN KEMISKINAN MELALUI PEMBERDAYAAN ZAKAT - Ahmad, Nur (ZISWAF, 2015)
Zakat is the property that must be set aside by a Muslim or body owned by a religion in accordance with the provisions to be given to those who deserve it. As Allah SWT. Meaning: “Those who believe do righteous deeds, to establish regular prayers and practice regular charity, they mendaoat Tuhanya rewarded. And there shall no fear come upon them neither shall they grieve “(Q.S. Al-Baqarah: 277). Zakat also has the function of a very high socioeconomic, relating to the prohibition of usury, zakat directed us not to accumulate treasures-stacked. Zakat is a means of educating for human possessions or material that is not the purpose of life and not a right of absolute property of the man who has it, but it is a surrogate of God, which should be used as a tool to control yourself to God and as a human being to run the commands of God in all aspects. If the potential of the Muslims in the empowerment of zakat are properly managed in an integrated and optimized, then the zakat funds can overcome the problems of poverty and reduce social disparities akam certainly capable of reducing poverty. However, this is no different than fire as far roast. Not according to what most people expected. In practice for the management of zakat is done individually but only a few institutions, the management of zakat implemantasinya not well ordered based on the principle of pilgrims, so that its collection is relatively small due to scattered everywhere without good management.